Clinical pathomorphism of chronic opisthorchosis pancreatitis - B. I. Alperovich; N. S. Rodicheva; Zh. A. Kurysko (Бюллетень сибирской медицины, 2004)
192 patients with chronic opisthorchosis pancreatitis (117 women (60,9%) and 75 men (39,1%) being under observation in Tomsk regional hepatologic center from 1970 till 2000) have been included in the protocol of retrospective cohort study. 36 patients (18,8%) have had a chronic pseudotumor-like pancreatitis. 133 patients (69,9%) have been diagnosed a chronic painful pancreatitis, 23 patients (12,0%) have been diagnosed a pancreatic cyst. Three basic forms of the chronic opisthorchosis pancreatitis have been suggested: a chronic painful pancreatitis, a chronic pseudotumor-like pancreatitis and a pancreatic cyst.